PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBASIS GAMIFIKASI DIGITAL TERHADAP MOTIVASI BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV DI MI DAARUL AITAM PALEMBANG - Tri Ajeng Nurjanah; Nurlaeli; Amir Hamzah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the digital gamification-based Talking Stick learning model on the learning motivation of fourth-grade students in Pendidikan Pancasila at MI Daarul Aitam Palembang. This research was motivated by the low level of students’ learning motivation in Pendidikan Pancasila, indicating the need for an innovative and engaging learning model that can encourage students’ active participation during the learning process. This study employed a quantitative approach with a Non-Equivalent Control Group Design. The subjects consisted of two classes: an experimental class that received treatment using the digital gamification-based Talking Stick learning model and a control class that received conventional learning methods. Data were collected through learning motivation questionnaires, observation, and documentation. The data were analyzed using a t-test with the assistance of SPSS version 31. The results showed that the digital gamification-based Talking Stick learning model had a significant effect on the learning motivation of fourth-grade students. This was indicated by the t-count value being greater than the t-table value at a significance level of 0.05. Therefore, it can be concluded that the implementation of the digital gamification-based Talking Stick learning model can improve students’ learning motivation in Pendidikan Pancasila at MI Daarul Aitam Palembang.